PENGARUH PROFITABILITAS, UKURAN PERUSAHAAN DAN RISIKO BISNIS TERHADAP STRUKTUR MODAL PADA PERUSAHAAN TEKSTIL DAN GARMENT YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2015-2020 - Royani, Ida; Sakti , Indra (GOVERNANCE: Jurnal Ilmiah Kajian Politik Lokal dan Pembangunan, 2023)
There are several factors that can affect capital structure, namely profitability, company size, business risk, growth opportunity, liquidity, asset structure and sales growth. This study examined the effect of Profitability, Firm Size, and Business Risk on the Capital Structure of Food and Beverage Companies on the Indonesia Stock Exchange (IDX) during 2015-2020. The samples in this study were 15 companies with 90 observations. This study used panel data, which was a combination of cross-section and time-series data. The data analysis method used was the Panel Data Regression analysis method with the Fixed Effect Model (FEM) panel estimation. The results found that profitability, firm size,and business risk had a negative and significant influence on capital structure